Circling the Circulatory - Checchia, Viviana (Peripeti, 2022)
This article offers a new term, ‘circulatory’ to foreground curatorial and artistic practices predicated on processual, interlacing strategies of public-becoming. The circulatory is evident in such practices neither ‘before’ nor ‘after’ but amidst a temporal, and often durational, interlinking of enquiry, making, and sharing, each element informed anew by the situation, locality, field of enquiry, and ambitions for dissemination. With reference to select examples, the circulatory is offered as a concept and practice and as a method of evaluating the efficacy of connection between all elements of artistic work on a trajectory from inception, through realisation, to becoming public.